Community Health Workers Bridging the Gap: Connecting Medicaid Members with Providers, Managed Care, and Community-Based Organizations - Austin S; Qu H (Risk Management and Healthcare Policy)
Shamly Austin,1 Haiyan Qu2 1Research, Development, & Analytics, Highmark Wholecare, Pittsburgh, PA, 15222, USA; 2Department of Health Services Administration, School of Health Professions, University of Alabama at Birmingham, Birmingham, AL, 35294, USACorrespondence: Shamly Austin, Research, Development & Analytics, Highmark Wholecare, 501 Penn Ave, Pittsburgh, PA, 15222, USA, Tel/Fax +1 412-420-6414, Email saustin@highmarkwholecare.comBackground: Community Health Workers (CHWs) are key to extending health care services, especially to marginalized communities to reduce challenges related to health care access. The study objective was to qualitatively explore the comprehensive role of CHWs in bridging the gap for Medicaid managed care organization (MCO) members’ access to health care providers, managed care, and community-based organizations to address health-related social needs (HRSN).Methods: We conducted a retrospective thematic analysis of narratives developed by CHWs on their role and Medicaid member lives. Three CHWs were embedded in four predominantly Black neighborhoods of Pittsburgh, Pennsylvania, by an MCO for six-months (January–June 2017) to connect its members with the managed care, health care system, and HRSN. In total, 46 MCO members remained throughout the program. The CHWs developed narratives on 13% (n = 6) of MCO members as part of a quality improvement project. These documented narratives became raw data for this study.Results: The age of MCO members ranged from 25 to 58 years and were Black (n = 6). The narrative had 50% of males and females. Three overarching themes in the narratives about CHWs’ role were improving members’ access to health care system (providers and medication), helping members with HRSN, and connecting members to managed care case management and member services.Conclusion: CHWs as MCO staff embedded in communities could help improve its members’ health care continuity, care coordination, and HRSN access. Our study demonstrates that CHWs are instrumental in bridging the gap between different systems for Medicaid MCO members. They play a crucial role in connecting the members to primary care providers, specialists, prescription drugs, MCO benefits, case management, and addressing their HRSN such as food, childcare, and housing. Future research should focus on program effectiveness by measuring member experience, health care utilization, health outcomes, and costs in Medicaid managed care settings.Keywords: qualitative research, community health workers, Medicaid managed care organization, Medicaid members, health-related social needs, community-based organizations